PENGARUH VARIABEL PREDIKTOR TERHADAP KEPATAHUAN PEMBAYAR ZAKAT DALAM MENINGKATKAN SUMBER DAYA MANUSIA PADA CIVITAS AKADEMI POLINEMA - Muhammad Muwidha; Mahmudatul Himma; Nur Indah (Adbis: Jurnal Administrasi dan Bisnis, 2019)
This study aims to obtain information about factors that influence adherence to pay zakat. The motivation of this research is related to the existence of POLINEMA facilities in the form of the An Nur Raya mosque which is adequate as a campus mosque that has been calculated in the Greater Malang area. Of course the service is not only in terms of mahdah worship but must immediately be empowered for social services, especially in contributing to creating prosperity for the community. The total research population of 234 personal sampling results as many as 114 personal. The questionnaire returned 60 answers. Findings obtained that 55% of POLINEMA employees have adjusted zakat payments. The remaining 45% is expected to be a potential muzakki in the future. Two important variables that influence adherence are Understanding Zakat and Transparency. Especially for transparency to have a stronger and significant influence The best step is to immediately set up an institution that manages zakat by preparing a variety of facilities both physical and necessary resources.